The effect of paternal psoriasis on neonatal outcomes: a nationwide population-based study - Huang, Yu-Huei; Chiou, Meng-Jiun; Yang, Shun-Fa; Kuo, Chang-Fu (Frontiers in Immunology, 2023)
Background Psoriasis is a chronic autoimmune disease involving both environmental and genetic risk factors. Maternal psoriasis often results in poor pregnancies that influence both mothers and newborns. However, the influence of paternal psoriasis on the newborn remains unknown. The aim of this study was to investigate whether paternal psoriasis is associated with increased risk of adverse neonatal outcomes, within a nationwide population-based data setting. Methods Singleton pregnancies were identified in the Taiwan National Health Insurance database and National Birth Registry between 2004-2011 and classified into four study groups according to whether mothers and spouses had psoriasis (paternal(−)/maternal(−), paternal(+)/maternal(−), paternal(−)/maternal(+), and paternal(+)/maternal(+)). Data were analyzed retrospectively. Adjusted odds ratios (aOR) or hazard ratios (aHR) were calculated to evaluate the risk of neonatal outcomes between groups. Results A total of 1,498,892 singleton pregnancies were recruited. Newborns of fathers with psoriasis but not of mothers with psoriasis were associated with an aHR (95% CI) of 3.69 (1.65–8.26) for psoriasis, 1.13 (1.06–1.21) for atopic dermatitis and 1.05 (1.01–1.10) for allergic rhinitis. Newborns of mothers with psoriasis but not of fathers with psoriasis were associated with an aOR (95% CI) of 1.26 (1.12-1.43) for low birth weight (<2500 g) and 1.64 (1.10–2.43) for low Apgar scores, and an aHR of 5.70 (2.71–11.99) for psoriasis. Conclusion Newborns of fathers with psoriasis are associated with significantly higher risk of developing atopic dermatitis, allergic rhinitis and psoriasis. Caution is advised for adverse neonatal outcomes when either or both parents have psoriasis.